The Effect of the Project-Based Learning (PjBL) Learning Model on Cooperative Ability and Physics Learning Outcomes of Students at Madrasah Aliyah Negeri 1 Jambi City - Febriya, Dhea; Fauzi, Ahmad; Desnita, Desnita (Fakultas Tarbiyah Institut Agama Islam Negeri (IAIN) Bone, 2023)
This research aims to determine the effect of the Project-Based Learning learning model on students' cooperative abilities and physics learning outcomes in the Parabolic Motion with Vector Analysis material at Madrasah Aliyah Negeri 1 Jambi City. This research is a Quasi-Experimental research and One Group Pretest-Posttest research design, so that the results of the treatment can be known more accurately because they can compare the situation before being given treatment and after being given treatment. Data collection was carried out using questionnaires and tests. The subjects in this research were all students of class XI 1 Madrasah Aliyah Negeri 1 Jambi City. The sampling technique uses Simple Random Sampling. Data processing and analysis techniques were carried out quantitatively using the paired t-test. The results of this research show that the Project-Based Learning (PjBL) learning model has an effect on students' cooperative abilities and physics learning outcomes with t- test results for both variables of 0,000 and N-Gain test results of 0,49 and 0,64.